Effects of Dietary Supplementation of Lactobacillus delbrueckii on Gut Microbiome and Intestinal Morphology in Weaned Piglets - Wang, Xiao-Long; Liu, Zhu-Ying; Li, Ying-Hui; Yang, Ling-Yuan; Yin, Jie; He, Jian-Hua; Hou, De-Xing; Liu, Ya-Li; Huang, Xing-Guo (Frontiers in Veterinary Science, 2021)
Lactobacillus delbrueckii is a gram-positive bacterium mostly used in the dairy industry for yoghurt and cheese. The present study was designed to evaluate the effects of Lactobacillus delbrueckii on serum biochemical parameters, intestinal morphology and performance by supplementing at a dietary level of 0.1% in diets for weaned piglets. Eighty healthy weaned piglets (initial body weight: 7.56 ± 0.2 Kg) were randomly divided into 2 feeding groups with 4 replicates in each group (n=10 animals per replicate), piglets were feed with ① Basal diet (CON) or ② Basal diet containing 0.1% Lactobacillus delbrueckii (LAC). The results showed that dietary supplementation of Lactobacillus delbrueckii improved growth performance and increased serum HDL and insulin levels in piglets at the 28th day of the experimental time (P<0.05). The gut microbe analysis revealed that Lactobacillus delbrueckii significantly decreased the relative abundance of phyla Bacteroidetes, but increased the relative abundance of phyla Firmicutes. The Lactobacillus delbrueckii also significantly increased the relative abundance of Bifidobacterium, Lactobacillus at the genus level of bacterial community in the ileum, but decreased the relative abundance of unclassified Clostridiales. Moreover, Lactobacillus delbrueckii improved mucosal morphology by obtaining higher intestinal villus height (P<0.05), significantly increasing the concentrations of butyrate, isobutyric acid and isovaleric acid in colonic chyme of piglets, but decreasing the intestinal pH at the duodenum and ileum at the 28th day of the experimental time. In conclusion, dietary supplementation of Lactobacillus delbrueckii in the diet of weaned piglets can improve intestinal morphology and modulate the microbiota community to promote growth performance.